2020
DOI: 10.14744/semb.2020.89983
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Transforaminal Epidural Steroid Injection in Lumbar Spinal Stenosis

Abstract: of Transforaminal Epidural Steroid Injection in Lumbar Spinal StenosisO ne of the degenerative pathologies of the lumbar spine is lumbar spinal stenosis (LSS) and it is a common cause of radicular pain. [1][2][3] The pathology appears as foramen, lateral recess and central stenosis on lumbar magnetic resonance image (MRI). The morphologic classification of LSS on lumbar MRI has been described by measuring the dural sac cross-sectional surface area in the literature. [4] The severe and extreme stenosis is treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The transforaminal epidural injection was reported to be a safe and effective treatment module as a nonsurgical treatment for LCS and LDH. [16] Many mechanisms have been described, such as that the corticosteroids stop the arachidonic acid production resulting in the inhibition of the pain-generating pathway or directly relieving central pain sensitization. Another possibility is that the nerve roots stretch due to injections in the epidural space, causing the lysis of neural adhesions, with more pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…The transforaminal epidural injection was reported to be a safe and effective treatment module as a nonsurgical treatment for LCS and LDH. [16] Many mechanisms have been described, such as that the corticosteroids stop the arachidonic acid production resulting in the inhibition of the pain-generating pathway or directly relieving central pain sensitization. Another possibility is that the nerve roots stretch due to injections in the epidural space, causing the lysis of neural adhesions, with more pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…[6] In contrast, Yuce et al and Donohue et al reported a decrease in pain scores in patients who underwent TFESI for the treatment of radicular low back pain; however, making a direct comparison with the findings of the present study is difficult. [1,4]…”
Section: Discussionmentioning
confidence: 99%
“…[6] In contrast, Yuce et al and Donohue et al reported a decrease in pain scores in patients who underwent TFESI for the treatment of radicular low back pain; however, making a direct comparison with the findings of the present study is difficult. [1,4] TFESI is an effective treatment modality for pain relief and functional improvement in patients with foraminal stenosis. [4] Olguner et al reported that 64% of the patients with foraminal stenosis experienced pain relief (pain score reduction of ≥50%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations